Community Economic Development through a Sufism Perspective In Indonesian Islamic Boarding School - Suhandi Suhandi; Gesit Yudha; Muhammad Jayus (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
This article explored how to develop a Sufism-based community economy at the Al- Hanif Islamic Boarding School in Bandar Lampung City, Indonesia. The authors used qualitative field research with a descriptive analysis technique to describe economic development. The results of this study were one of the teachings highly emphasized in the Sufism-based Islamic boarding school conducted by Al-Hanif Lampung is the belief that religious perfection consists of three dimensions: Imān, Islām, and Iḥsān. Economic development in the Boarding School community empowerment process is carried out independently without assistance from the government through Bait al-Māl wa Tamwīl (BMT), drinking water companies, and schools. This Islamic Boarding School also applies the Islamic economic system in its business, such as the profit-sharing (muḍārabah) system, and prioritizes community empowerment to benefit the surrounding community. Moral Sufism values are implemented in the industrial economy, including the concepts of Ikhlāş ‘sincerely’, zuhd ‘asceticism’, takhalī (emptying the heart from despicable qualities), tahalī (filling the heart from commendable qualities), and tajalī (self-approach to Allah). The business aims to open up employment opportunities for the local community, which will later bring prosperity to the community; a profit-sharing system is also implemented in the trading system; whatever profits are obtained will be shared with the manager, and then the existing profits will be used for operations and activities that benefit the local community. Running an independent business will become a source of income for carrying out religious activities and become a job opportunity for the local community. Practicing the concept of Sufism in a modern ascetic manner is also hoped that it can foster spiritual values.